La justicia de paz y acceso al registro de las escrituras imperfectas - Ortiz Pasco, Jorge (Revista de Derecho, 2019)
The author of this text makes a description of the functioning of an institution that is sometimes set aside of the legal literature: the Justice of the Peace. Justice of the Peace is a judicial authority that has a great importance in Peru, given the number of people that are not able to come before regular courts, in order to solve their controversies. This text does not focus in the role of the Justice of the Peace in solving controversies, but in its role to act as a Notary Public. In that sense, incities or provinces where there is not a Notary Public, this role is fulfilled by the Justice of the Peace. Among the Notary tasks assumed by the Justice of the Peace is to issue public deeds, which have basically the same quality as the ones that any Notary Public would issue. These instruments, that are called “imperfect public deeds”, have been the matter of a series of binding precedents by the “Tribunal Registral”, the public entity in charge of reviewing –as a last stage of proceeding– the decisions of the registrars relating to imperfect public deeds. The author refers to them in an effort to explain the context, the history and the importance of the role of the Justice of the Peace in Peru.